2017
DOI: 10.1002/smll.201703006
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport in 2D DNA Tunnel Junction Diodes

Abstract: Recently, deoxyribonucleic acid (DNA) is studied for electronics due to its intrinsic benefits such as its natural plenitude, biodegradability, biofunctionality, and low-cost. However, its applications are limited to passive components because of inherent insulating properties. In this report, a metal-insulator-metal tunnel diode with Au/DNA/NiO junctions is presented. Through the self-aligning process of DNA molecules, a 2D DNA nanosheet is synthesized and used as a tunneling barrier, and semitransparent cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Here, E g is defined by the energy difference between the HOMO and LUMO levels in a sample, as shown at the bottom of Figure i. By using a known q ϕ (i.e., q ϕ Ag of 4.26 eV, q ϕ ITO of 4.8 eV, and q ϕ DNA of 4.54 eV) and E g , we evaluate the unknown q ϕ DNA+CuO as 4.83 eV . We introduce the work-function barrier height ( q ϕ B ), which depends on the movement of the charge carriers in accumulation, depletion, and inversion regions (Figure j).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, E g is defined by the energy difference between the HOMO and LUMO levels in a sample, as shown at the bottom of Figure i. By using a known q ϕ (i.e., q ϕ Ag of 4.26 eV, q ϕ ITO of 4.8 eV, and q ϕ DNA of 4.54 eV) and E g , we evaluate the unknown q ϕ DNA+CuO as 4.83 eV . We introduce the work-function barrier height ( q ϕ B ), which depends on the movement of the charge carriers in accumulation, depletion, and inversion regions (Figure j).…”
Section: Resultsmentioning
confidence: 99%
“…By using a known qϕ (i.e., qϕ Ag of 4.26 eV, qϕ ITO of 4.8 eV, and qϕ DNA of 4.54 eV) and E g , we evaluate the unknown qϕ DNA+CuO as 4.83 eV. 42 We introduce the work-function barrier height (qϕ B ), which depends on the movement of the charge carriers in accumulation, depletion, and inversion regions (Figure 8j). The flow of the charge carriers in the device strongly depends on the polarity of the applied V. In the accumulation condition (V > 0, e.g., at 2 V), the negative charge carriers (electrons) are attracted toward and accumulate at the interfacial layer between the electrode and the dielectric material (either DNA or DNA+CuO).…”
Section: Introductionmentioning
confidence: 99%
“…By viewing the I−V data in a ln(I/V 2 ) versus 1/ V form, the transition between FN tunneling and TE injection is observed by the minimum in the ln(I/V 2 ) curve. 2, 45 The temperature dependence of the 900 °C MoS 2 devices is shown in Figure 4a. From inspection, two distinct features are immediately visible in the data.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Im et al applied a two-dimensional double-crossover DNA lattice with a thickness of a few nanometers while maintaining a macroscopic area (3 × 10 5 μm 2 ) and showed that it operated stably as a tunneling diode. 21 This result suggests that the recent megadalton-sized 3D structures, that is, DNA bricks, 22 are also promising as semiconductor materials. Stable and robust electrical access to a single DNA molecule remains a nanotechnology challenge, and bottom-up nanofabrication using preassembled DNA nanostructures will be the key to solving it.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Studies about the assemblies of conventional metal/insulator/metal-type devices were also reported. Im et al applied a two-dimensional double-crossover DNA lattice with a thickness of a few nanometers while maintaining a macroscopic area (3 × 10 5 μm 2 ) and showed that it operated stably as a tunneling diode . This result suggests that the recent megadalton-sized 3D structures, that is, DNA bricks, are also promising as semiconductor materials.…”
Section: Introductionmentioning
confidence: 99%